PEMANFAATAN BIJI LABU KUNING (Cucurbita moschata) UNTUK PEMULIHAN MORFOLOGI DAN MOTILITAS SPERMATOZOA MENCIT (Mus Musculus) YANG TERPAPAR 2-METOKSIETANOL - Alfiah Hayati; Nina Puspita; I.B. Rai Pidada (The East Java Biological Society, 2012)
Research has done to investigate the effect of pumpkin seed extract on morphology and motility of the mices after given of 2-ME. Thirty male mices, 56–63 days with 23–27 g weight were used as experimental animals into 5 groups (2 groups is control and 3 groups is treatment), 6 mices each. The fi rst group is K0 which given 0.1 mL aquades by gavage for 40 days each day, and then K1 were given 0.05 mL 2-ME 200 mg/kg by intraperitoneally everyday within 5 days, and continued on the giving of aquadest. The next groups are treated groups which given 2-ME, in the fi rst 5 days, then continued to the givings of pumpkin seed extract by gavage. Cucurbita moschata seed extract were given in three doses: 0.5; 1.0; and 2.0 g/kg BB for 35 days. Sperm collected from cauda epididymis. Parameter of sperm quality are morphology and motility. The result shown that Cucurbita moschata seed extract doses 0.5–1.0 g/kg BB showed no significant effect and then doses 2.0 g/kg BB increased recovery process morphology and motility with signifi cant differences p < 0.05. The conclutions were Cucurbita moschata seed extract increased recovery process morphology and motility of the mices.